Performance Evaluation of Equity-based Unit Trusts in Singapore - Magogo, Annette (2010)
The development of mutual funds has a substantial contribution in the financial literature. This significant financial innovation has drawn attention of both academicians and practitioners to undertake different investigation in the mutual fund industry. In a similar way, this empirical study evaluates the performance of thirty equity based unit trusts in Singapore market for the period starting from February 2000 to December 2006. In this study, monthly data are used to evaluate the performance of the funds using risk adjusted measures, namely, Sharpe ratio and Jensen alpha originating from the Capital Asset Pricing Model. Additionally, this study evaluates performance in terms of the selectivity and market timing skills possessed by the fund managers. In overall, the empirical results show that the funds underperformed compared to the market benchmark. Accordingly, the funds do not have selectivity and market timing abilities. This study also provides a brief discussion on the research issues encountered in performance evaluation procedures, mainly, survivorship bias and appropriate benchmarking.